THE INFLUENCE OF WORK EXPERIENCE, KAIZEN CULTURE, AND COMPETENCE ON EMPLOYEE PERFORMANCE MUSHROOM MSMES IN KEDIRI - Erwin Syahputra; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This research seeks to explores the influence of work experience, kaizen culture, and competence on the performance of employees in Mushroom Micro, Small, and Medium-Sized Enterprises (MSMEs) in Kediri. The study encompassed the entire population of MSME Mushroom employees in Kediri, totaling 45 individuals, employing a saturated sampling technique where all respondents were considered as samples. Data collection methods involved observation, interviews, questionnaires, and literature studies, with data measurement conducted through the Likert scale. Analysis of the collected data employed validity tests, reliability tests, multiple linear regression tests, t tests, F tests, and the coefficient of determination, facilitated by SPSS 16.0. The results of the multiple linear regression analysis indicated that all independent variables significantly influenced the dependent variable, which is employee performance. The coefficient of determination revealed a percentage of 70.9%, signifying that work experience, kaizen culture, and competence collectively account for this portion of the variance in the performance variable. The remaining 29.1% is attributed to other variables not scrutinized in this research. These findings highlight the substantial influence of the specified factors on employee performance within the context of Mushroom MSMEs in Kediri.